2022
DOI: 10.1021/acsaem.2c03332
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Organic Photothermal Material Based on Fusion of the Donor–Acceptor Structure for Water Evaporation and Thermoelectric Power Generation

Abstract: Recently, organic photothermal materials have shown great application potential for solar-driven water−electricity co-generation. However, their extended application is limited by low solar-heat conversion efficiency. This study designed a planarized donor−acceptor (D−A)-type organic photothermal material 5,18-dibutyl-5,18-dihydrodiquinoxaline[2,3-a:2′,3′-c]phenazine (DDHT) by fusing a strongly electron-donating arylamine unit and strongly electron-withdrawing quinoxalino[2,3-a]phenazine unit. The fused-ring D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…S9, ESI †). Compared with other organic photothermal materials, 14,[34][35][36]62 the photothermal conversion efficiency of the 2TP-BBT material is good (Table S2, ESI †).…”
Section: Tp-bbt For Water Evaporation Performancementioning
confidence: 99%
See 1 more Smart Citation
“…S9, ESI †). Compared with other organic photothermal materials, 14,[34][35][36]62 the photothermal conversion efficiency of the 2TP-BBT material is good (Table S2, ESI †).…”
Section: Tp-bbt For Water Evaporation Performancementioning
confidence: 99%
“…The evaporation rate of the water–electric cogeneration device is 1.22 kg m −2 h −1 , and the output voltage is 57.1 mV. Comparing the thermoelectric properties of reported organic photothermal materials, 34–37 it is found that the thermoelectric power generation properties of the 2TP-BBT material are excellent (Table S1, ESI†). The thermoelectric power generation and water–electricity cogeneration under solar illumination offer a valuable prospect of utilization in efficient solar thermal energy conversion to solar water evaporation and power generation applications.…”
Section: Introductionmentioning
confidence: 95%
“…The PDI core with planar and rigid multi-ring 𝜋electron conjugation system causes PDI-DTMA molecule to aggregate through intermolecular 𝜋-𝜋 interaction, favorable for broadening the absorption spectrum and strengthening the photothermal conversion. [9,12,15,16,18] Additionally, the electrondonating 3,4,5-trimethoxyphenyl moieties are strategically attached to the imide positions of the electron-accepting PDI core, resulting in the D-A-D configuration of PDI-DTMA. [27,28] The modification of the electron donor to the acceptor can reduce the band gap, so as to achieve the optimization of light absorption and photothermal conversion.…”
Section: Synthesis and Characterization Of Pdi-dtmamentioning
confidence: 99%
“…Strategies, such as regulation of molecular stacking, enhancement of intramolecular charge transfer, introducing intramolecular motion and free radicals, have been employed to narrow the band gap, thereby maximizing photothermal conversion efficiency. [10][11][12][13][14][15][16][17][18][19] Despite these efforts, the number of available organic small molecules for solar water evaporation remains limited. Additionally, most of these evaporators lack subtle design, resulting in unsatisfactory water evaporation rates (<1.55 kg m −2 h −1 under 1 kW m −2 ), which are lower than recently reported evaporation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the common organic photothermal materials are organic small molecular dyes of porphyrin, 11 indocyanine green, 12 and phthalocyanine 13 and polymers of polyaniline (PAN), 14 polydopamine 10,15 and polypyrrole (PPY), 16 diketone pyrrole, 17 and other donor-acceptor conjugate compounds. 18,19 However, the electron localization characteristic of organic materials makes fine-scale tunability in band structure difficult, which brings challenges to molecular design and organic synthesis process.…”
Section: Introductionmentioning
confidence: 99%